Seminar on integration and rapid transit delegate information : Wednesday 23 June 1999 (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Croydon on 23 June 1999.